Pengaruh Konsumsi Abon Jantung Pisang terhadap Peningkatan Produksi ASI pada Ibu Menyusui di Wilayah Kerja UPT. Puskesmas Damai - Leolita, Elsa; Endah Wahyutri; Hesti Prawita Widiastuti (Indonesian Journal of Nursing Research (IJNR), 2023)
Coverage of exclusive breastfeeding in the working area of UPT. Damai Health Center is still relatively low, this is due to insufficient milk production. Lactagogum is a substance that can increase the production of breast milk, which laktagogum is found in shredded banana blossoms.  The research used the experimental research with design quasi-experimental and time series research design is one group pre and post test without control . The sample of this research is breastfeeding mothers in the working area of UPT. The Damai Health Center is 18 people. The sampling technique used purposive sampling. Instrumen of research is observation paper. Data analysis  using paired t test ( paired sample t test ). After being given 200 grams of shredded banana flower with a frequency of 2 times a day for 7 days, the mean difference before and after consuming shredded banana heart on the first day was 8.33 and the p value was 0.014 <0.05. Ha accepted there is an effect of consumption of shredded banana to increasing milk production in breastfeeding mothers in the UPT work area.Damai Health Center. Abstrak   Cakupan ASI Ekslusif di wilayah kerja UPT. Puskesmas Damai masih relatif rendah, ini disebabkan produksi ASI yang tidak mencukupi. Laktagogum merupakan zat yang dapat meningkatkan produksi ASI, yang mana laktagogum terdapat pada abon jantung pisang. Jenis penelitian ini adalah eksperimental dengan rancangan quasi eksperimen dan desain penelitian time series one grup pre and post test without control. Sampel penelitian ini adalah ibu menyusui di wilayah kerja UPT. Puskesmas Damai berjumlah 18 orang. Teknik sampling  menggunakan purposive sampling. Instrumen penelitian ini adalah lembar observasi. Analisis data yang digunakan uji t berpasangan (paired sampel t test). Hasil Penelitian setelah diberikan abon jantung pisang sebanyak 200 gram dengan frekuensi 2 kali sehari selama 7 hari didapatkan hasil p value yaitu 0,014 < 0,05. Ha diterima menunjukan ada pengaruh konsumsi abon jantung pisang terhadap peningkatan produksi ASI pada Ibu menyusui di wilayah kerja UPT. Puskesmas Damai